A Dynamic Model of Weak and Strong Ties in the Labor Market - Zenou, Yves (Journal of Labor Economics, 2015)
The study develops a simple model where workers can obtain a job through either their strong or weak ties. It shows that increasing the time spent with weak ties raises the employment rate of workers. It also shows that when the job-destruction rate or the job-information rate increases, workers choose to rely more on their weak ties to find a job. The model is extended so unemployed workers can also learn of a vacancy directly from an employer. Results show that equilibrium employment and time spent with weak ties are sometimes, but not in all cases, positively related.